Eros and Thanatos reflection in the works of English Methaphysical poets: comparative analysis of selected lyrics by John Donne (1572 – 1631) and Andrew Marvell (1612 – 1678) - Смольницька, Ольга Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article analyses selected love lyrics by John Donne and Andrew Marvell by is given. The implicit meanings of the texts are considered. The religious sense and the reflection of the ritual in these poems are emphasized. The Bible, Occitan courtly poetry, folk English and Scottish ballads are involved as consources. It is proved that Eros as vitalistic desire and Thanatos as the death drive are linked. Textual, contextual, intermedial, macro- and microcontextual analysis is made.